Slit‐Robo signalling establishes a Sphingosine‐1‐phosphate gradient to polarise fin mesenchyme. (9th June 2022) - Mahabaleshwar, Harsha; Asharani, PV; Loo, Tricia Yi; Koh, Shze Yung; Pitman, Melissa R; Kwok, Samuel; Ma, Jiajia; Hu, Bo; Lin, Fang; Li Lok, Xue; Pitson, Stuart M; Saunders, Timothy E; et al.
Abstract: Immigration of mesenchymal cells into the growing fin and limb buds drives distal outgrowth, with subsequent tensile forces between these cells essential for fin and limb morphogenesis. Morphogens derived from the apical domain of the fin, orientate limb mesenchyme cell polarity, migration, division and adhesion. The zebrafish mutant stomp displays defects in fin morphogenesis including blister formation and associated loss of orientation and adhesion of immigrating fin mesenchyme cells. Positional cloning of stomp identifies a mutation in the gene encoding the axon guidance ligand, Slit3. We provide evidence that Slit ligands derived from immigrating mesenchyme act via Robo receptors at the apical ectodermal ridge (AER) to promote release of sphingosine‐1‐phosphate (S1P). S1P subsequently diffuses back to the mesenchyme to promote their polarisation, orientation, positioning and adhesion to the interstitial matrix of the fin fold. We thus demonstrate the coordination of the Slit‐Robo and S1P signalling pathways in fin fold morphogenesis. Our work introduces a mechanism regulating the orientation, positioning and adhesion of its constituent cells. Synopsis: The Slit‐Robo signalling pathway is required for proper morphogenesis of the zebrafish fin and acts upstream of sphingolipid signalling to promote polarity, directional migration and adhesion of the constituent mesenchymal cells. The Slit‐Robo pathway establishes a sphingosine‐1‐phosphate signal in the zebrafish larval fin Loss of either pathway leads to defects in haptotaxis of fin mesenchyme including loss of adhesion, polarity and migration. The reciprocal signalling system permits migrating mesenchymal cells to tune their adhesive properties as they approach the fin apex. Abstract : The Slit‐Robo signalling pathway is required for proper morphogenesis of the zebrafish fin and acts upstream of sphingolipid signalling to promote polarity, directional migration and adhesion of the constituent mesenchymal cells.